Perancangan dan Realisasi Sistem Kendali Furnace Menggunakan Ratio Control Berbasis Distributed Control System Centum VP R05.04.20 - Najmurrokhman, Asep; Listi Restu Triani (EPSILON: Journal of Electrical Engineering and Information Technology, 2025)
In the oil and gas processing industry, a reliable control system is essential to ensure energy efficiency and operational safety. One of the critical elements is the control of the air-to-fuel ratio in the combustion process of the furnace. This study aims to design and implement a furnace control system using a ratio control strategy based on the Yokogawa Distributed Control System (DCS) Centum VP R5.04.20. The system is designed to precisely regulate the mass flow rates of air and fuel to achieve optimal combustion efficiency and minimize emissions. Control is executed via PID configuration within the DCS, with parameter tuning optimized to maintain process stability. The implementation results indicate that the system operates under stable conditions with a ratio gain of 2.5, and PID parameters for FIC102 (P=100, I=10, D=0) and PIC201 (P=180, I=60, D=0). The system successfully improves control response and furnace operational efficiency, while also providing a foundation for the future adoption of more advanced automation systems.